2017
DOI: 10.3892/ol.2017.6920
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of semaphorin 3C suppresses cell proliferation and migration in MCF‑7 breast cancer cells

Abstract: Previous studies have suggested that semaphorin 3C (SEMA3C) is involved in the tumorigenesis and metastasis of a number of types of cancer. The aim of the present study was to investigate the role of SEMA3C in the proliferation and migration of MCF-7 breast cancer cells. Small interfering (si)RNA sequences targeting SEMA3C were constructed and transfected into MCF-7 cells in order to silence the expression of SEMA3C. Cell proliferation and migration were measured using CCK-8 and Transwell assays, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…To our knowledge, with the exception of SEMA3G, all SEMA3 family members have been at least partially studied in breast cancer. Most members showed tumour inhibiting roles while only SEMA3E was found to promote tumour invasion and metastasis [13,15,20,[35][36][37][38][39][40][41][42][43][44]. However, as mentioned above, most of the studies were conducted in cell lines or animal models.…”
Section: Sema3 Gene Family In Breast Cancermentioning
confidence: 99%
“…To our knowledge, with the exception of SEMA3G, all SEMA3 family members have been at least partially studied in breast cancer. Most members showed tumour inhibiting roles while only SEMA3E was found to promote tumour invasion and metastasis [13,15,20,[35][36][37][38][39][40][41][42][43][44]. However, as mentioned above, most of the studies were conducted in cell lines or animal models.…”
Section: Sema3 Gene Family In Breast Cancermentioning
confidence: 99%
“…Also, SEMA3C is highly upregulated and oncogenic in various types of cancers, including glioblastoma, prostate cancer, and breast cancer. Studies have revealed that SEMA3C promotes tumor cell proliferation, epithelial-to-mesenchymal transition, or sustains cancer stemness [14,[22][23][24][25]. Because PKD epithelial cells have similar properties to cancer cells such as sustained proliferative and inflammatory signaling [26], it is as- Fig.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, it is unclear if the R745A mutant is able to interact with the receptor neuropilin and if it is still able to activate signaling pathways (e.g., VEGFR and Rac1 activation pathways) within the cells. Zhu and coauthors demonstrated that the knockdown of SEMA3C significantly inhibited breast cancer cell MCF-7 growth and migration ( 20 ); therefore, it would be interesting to examine how the Sema3C R745A mutant affects the endothelial cell migration process. These studies would help to disclose the significance of the Sema3C protein furin cleavage site 742 RNRR 745 in molecular processes.…”
Section: Discussionmentioning
confidence: 99%